Development and complex characterization of bio-tribological Cr/CrN + a-C:H (doped Cr) nano-multilayer protective coatings for carbon–fiber-composite materials. Issue 13 (14th February 2015) - Major, L.; Janusz, M.; Kot, M.; Lackner, J. M.; Major, B.
<x xml:space="preserve">Abstract</x> Microstructure characterization of an as deposited coating; (a) image obtained using SEM; (b) image done by TEM technique in STEM mode. Microstructure characterization of the coating at the cross-section, done by TEM; (a) TEM BF image; (b) STEM image.